A new case of scalp angiosarcoma revealed by eyelid edema - Maha Mouradi; Fatima Zahra Elfatoiki; Fouzia Hali; Farida Mernissi; Sara Moukhlis; Soumiya Chiheb (Our Dermatology Online, 2022)
Cutaneous angiosarcoma is a rare and highly aggressive neoplasm with poor prognosis. Owing to its variable presentation, it may be a challenging clinical and histological diagnosis. Herein, we describe a particular case of cutaneous angiosarcoma of the head and neck in a 71-year-old male with skin type V who presented with solid, progressive eyelid edema. A histological examination of skin biopsies first concluded cutaneous metastasis of an undifferentiated carcinomatous tumor. Immunostaining was essential to reach the correct diagnosis. The treatment of cutaneous angiosarcoma remains unsatisfactory. We sincerely hope that the prognosis of cutaneous angiosarcoma will be improved with the use of targeted therapies based on current genetic studies as it has been for melanoma.